Pengaruh Perdagangan Maritim terhadap Penyebaran Islam di Indonesia pada Abad ke-15 M hingga ke-17 M - Sari, Ika Purnama; Putri, Shella Ananda; Ananda, Risky Dwi; Andira, Bagas Ibnu; Manalu, Agrifa Ido Arta; Zalukhu, Desveronika (Polyscopia, 2024)
The spread of Islam in Indonesia is a complex and diverse phenomenon, influenced by various historical, social, and economic factors. One factor that has an important role in the spread of Islam in Indonesia is maritime trade. This research aims to explore the influence of maritime trade on the spread of Islam in Indonesia. Through a historical approach and historical data analysis, this research explores maritime trade routes which were the main means of spreading Islam in Indonesia in the past. By paying attention to economic, social, and cultural factors related to maritime trade, this research discusses how trade via maritime routes has facilitated cultural and ideological exchanges, including the Islamic religion, in the Indonesian archipelago. The findings of this research reveal significant insights into how maritime trade facilitated the spread of Islam, highlighting specific trade routes and interactions that were crucial in this process, thus providing a deeper understanding of the relationship between maritime trade and the spread of Islam, as well as its relevance in the context of Indonesian history and social development.